2010
DOI: 10.1111/j.1524-4733.2009.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Method of Translation of Patient-Reported Health Outcome Questionnaires: A Randomized Study of the Translation of the Rheumatoid Arthritis Quality of Life (RAQoL) Instrument for Sweden

Abstract: The DP approach showed advantages over FB translation in terms of preference by the target population and by lay people, whereas there were no obvious psychometric differences. This suggests advantages of DP over FB translation from the patients' perspective, and does not support the commonly held view that FB translation is the "gold standard."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 20 publications
2
78
1
4
Order By: Relevance
“…This method has been used in the adaptation of all needs-based measures of QoL [14]. A recent study has shown that the ''dual panel'' methodology produces translations that are more acceptable to patients than forwardebackward translation [16].…”
Section: Translation Of the Lcopdmentioning
confidence: 99%
“…This method has been used in the adaptation of all needs-based measures of QoL [14]. A recent study has shown that the ''dual panel'' methodology produces translations that are more acceptable to patients than forwardebackward translation [16].…”
Section: Translation Of the Lcopdmentioning
confidence: 99%
“…Hedin et al [21] verwendeten die Rück-übersetzungstechnik, während die andere Version nach der Dual-Panel-Methode erfolgt war [22]. Hagell et al [23] führ-ten einen systematischen Vergleich beider Fassungen durch und fanden bei dem 30 Punkte umfassenden Fragebogen 7 identisch und 23 unterschiedlich übersetzte Punkte. Die unterschiedlich übersetzten Punkte wurden verschiedenen Gruppen im Hinblick auf Verständlichkeit und Wortwahl zur Beurteilung vorgelegt [23].…”
Section: Deutsche Endversion Der Stard-kriterienunclassified
“…Within the context of PROMs this method has been shown to outperform the commonly used forward-backward translation procedure (i.e., translation into the target language followed by back-translation into the source language) in terms of acceptability of the resulting translation (Hagell et al 2010). According to the DP approach, the new language version is produced by means of two panels, a bilingual panel (to provide the initial translation into the source language) and a lay-panel (where the initial translation is assessed for clarity and acceptability of language).…”
Section: Translation and Adaptation Proceduresmentioning
confidence: 99%